Pengembangan E-Modul Interaktif Berbasis Flipbook dalam Pembelajaran Mekanika Tanah di Departemen Teknik Sipil Universitas Negeri Padang - Aidil Rizki; Laras Oktavia Andreas (Unversitas Negeri Padang, 2025)
This research is based on the absence of an e-module that can used by students in the Soil Mechanics course at the Civil Engineering Departement of Padang State University, the students have difficulty learning and understanding Soil Mechanics material independently. To overcome this issue, a learning media product in the form of a Flipbook-based E-Module was developed with the help of Canva and Heyzine Online Flipbook Maker for Soil Mechanics learning. The purpose of this research is to develop a product in the form of Flipbook-based E-Module for valid and practical Soil Mechanics learning. The type of this research is Research and Development (R&D) using the ADDIE development model. The developed product is tested for its validity by expert lecturers in content and media. Then after being declared valid, a practicality test of the product is conducted by 25 students from the Civil Engineering Departement. The final results of the material expert validation obtained a coefficient value of 0,96 with the category “Very Valid” and the final results of the media expert validation obtained a coefficient value of 0,89 with the category “Very Valid”. The final results of the practicality test for the students obtained a value of 91,56% with the category “Very Practical”. Based on the results obtained, it can be concluded that the Flipbook-based E-Module media in Soil Mechanics learning developed is valid and practical for used by students of the Civil Engineering Departement at Padang State University